1989
DOI: 10.3801/iafss.fss.2-15
|View full text |Cite
|
Sign up to set email alerts
|

State Of Fire Research And Safety

Abstract: A review is made of available international statistics on the costs and losses due to fire. Estimates are also made on the level of fire research carried out by different countries. Views are presented on strategies for reducing the losses and costs by fire. An example is given to illustrate a rational use of test data to predict fire growth on materials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

1993
1993
2013
2013

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…The reason it does this is probably because of the formation of vortices, as first hypothesized by Williamson et al (1984), and demonstrated for the comer fire by Satoh (1989). Quintiere (1988) described an experiment carried out by B. Lee in 1988 (see Figure 6). The back wall of an ASTM enclosure (2.44x3.56x2.44 m -i.e., 8x12x8 feet -see Anon., 1983Anon., , 1993 was partially covered by 6.35 mm-thick (1/4") sheets of PMMA in the shape of a "T."…”
Section: Flame Length Greater Than the Wall Heightmentioning
confidence: 86%
“…The reason it does this is probably because of the formation of vortices, as first hypothesized by Williamson et al (1984), and demonstrated for the comer fire by Satoh (1989). Quintiere (1988) described an experiment carried out by B. Lee in 1988 (see Figure 6). The back wall of an ASTM enclosure (2.44x3.56x2.44 m -i.e., 8x12x8 feet -see Anon., 1983Anon., , 1993 was partially covered by 6.35 mm-thick (1/4") sheets of PMMA in the shape of a "T."…”
Section: Flame Length Greater Than the Wall Heightmentioning
confidence: 86%
“…The "T" pattern also occurs during fire growth on a fiat wall. Quintiere (1989) shows this pattern in photographs of a full-scale room-fire test in which a line-burner on the fioor ignited the central section of a PMMA-lined wall beneath a non-combustible ceiling.…”
mentioning
confidence: 93%
“…After the Montreal Convention was signed in 1987, the worldwide are seeking the Halon replacement product actively, such as water spray, CO 2 and foam technology research, but there are still no entirely appropriate alternative products. Water mist fire suppression technology occupies an important position in the sprinkler system for it's no environmental pollution, rapid extinguishment of fire, having been regarding as the main alternative product [1][2][3] of the Halon series extinguishing. Water mist demonstrate has broad application prospects in special fire prevention of high-tech fields and major industrial danger.…”
Section: Introductionmentioning
confidence: 99%